Application of Capacity Spectrum Method (CSM) for non-symmetrical reinforced concrete high-rise buildings as a tool for seismic design - Ayuddin, Ayuddin; Bindhu, K. R. (SINERGI, 2023)
The development of earthquake resistance design of structures in the last decade has been critically changing from strength and ductility to performance criteria, where the structure is decided for various levels of structural performance. To understand the structural performance because, at time, a large earthquake load on the structure will experience structural yielding, non-linear analysis with the capacity spectrum method will be performed. The relationship between roof displacement and base shear force is described by a curve that describes the structural capacity is a capacity curve. To determine the behavior of the structures under review for a given earthquake intensity, the capacity curve is then compared with the performance demand based on various earthquake intensities. The results of the case studies for reinforced concrete portals non-symmetrical 3D concluded that the convergence obtained at the point of the structure performance is   and . The displacement results for the actual structure () were 286.71 mm and building base shear coefficient was 15.46 %.